Evaluating the Effectiveness of Remote Mobile Health Services for the Elderly: Standards and Best Practices - Bo Wang; Peng Yang; Lidan Zhang; Yiping Zhang; Xuemei Li, (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The innovative application of emerging mobile and wearable health information and sensing technologies (mHealth) holds great promise for lowering healthcare costs and enhancing well-being in various ways. Numerous fields are seeing the development of these applications. Still, to fully understand the opportunities and difficulties associated with using mobile technologies to enhance health outcomes, more thorough research is required. There is currently little data supporting the effectiveness of mHealth. Even though these technologies seem harmless and enticing, more research is required to determine the best times, locations, and users for mHealth methods, applications, and devices. As a result, a remote medical hub waitperson is essential to sustainably providing high-quality telemedicine services. This paper offers a thorough analysis of the delivery of medical services through telemedicine applications, with a focus on medical center servers. It also draws attention to the problems and obstacles that still need to be resolved to deliver health services via telehealth in the medical center. These ideas are used in this work to define a high standard for the developing field of mHealth research, explore potential future directions, and describe existing assessment standards.